Using Restricted Bond Rotations to Enforce Excited-State Behavior of Organic Molecules - Kandappa, Sunil Kumar; Ahuja, Sapna; Singathi, Ravichandranath; Valloli, Lakshmy Kannadi; Baburaj, Sruthy; Parthiban, Jayachandran; Sivaguru, Jayaraman (Synlett, 2022)
This account highlights the role of restricted bond rotations in influencing the excited-state reactivity of organic molecules. It highlights the photochemical reactivity of various organic molecules and the design strategies that could be exploited by chemists to utilize restricted bond rotations to uncover new excited-state reactivity and to achieve selectivity.1 Introduction.2 NEER-Principle and Restricted Bond Rotations in the Excited State3 [2+2]-Photocycloaddition of Enamides4 [3+2]-Photocycloaddition vs. Paternò–Büchi Reaction of Enamides5 Divergent Photoreactivity of Enones Dictated by Restricted Bond Rotations: Norrish–Yang reactions vs. 6π-Photocyclization6 Divergent Photoreactivity of Imides with Alkenes: [2+2]-Photocycloaddition vs. Photoene Reaction7 Summary and Outlook
Keywords: photocycloaddition; axial chiral transfer; excited-state reactivity; photocatalysis; energy transfer catalysis